Characteristics of Cardioembolic Stroke Patient in Neurologic Ward Dr. Hasan Sadikin General Hospital Bandung - Adriana Damayanti; Lisda Amalia; Reza W. Sudjud (Universitas Kristen Maranatha, 2018)
Stroke is the second most common cause of death worldwide after heart disease. About80% stroke cases are ischemic stroke. One of 4 people with ischemic stroke had cardioembolicstroke. Ninety percent of cardiac emboli obstruct cerebral blood vessels and causedneurological deficit. Cardioembolic stroke may be due to abnormalities in cardiac walls,rhythm, valve, or function. Stroke patients with cardiac abnormalities have poor prognosis. Thisretrospective descriptive study was done in May-June 2017. We collected 103 medical recordsof stroke patients from Department of Neurology, Dr. Hasan Sadikin General Hospital duringJanuary 2015- March 2016. Data regarding sex, age, education level, economic status, andcardiac abnormalities were recorded. Majority of subjects were female (53.4%). The mostfrequent age group was 45-65 years old (49.51%). Most subjects had low educational level(76.7%) and low economic status (77.67%). Among subjects, 41.75% had cardiac rhythmabnormalities, 29.13% had cardiac wall abnormalities, 14.56% had cardiac valveabnormalities, and 14.56% had cardiac function abnormalities. The most common cause ofcardioembolic stroke was atrial fibrillation.Keywords: cardioembolic stroke epidemiology, patient characteristics, cardiac disease